Il progetto DigitALI: problemi e prospettive della digitalizzazione dell’Atlante Linguistico Italiano (ALI) - Cerruti, Massimo; Ferrarotti, Lorenzo; Fiori, Stefano; Rivoira, Matteo; Turchetta, Barbara (Linguistik Online, 2025)
The paper aims to describe the main methodological issues in the digitization of the Atlante Linguistico Italiano (ALI), a fundamental resource for dialectological research on the dialects of Italy. Despite its scientific relevance, ALI remains difficult to access due to its printed format and heterogeneous data structure. The project seeks to overcome these limitations by developing a structured, queryable database integrated into a digital cartographic interface. This paper presents the main methodological challenges encountered in the digitization process, including data standardization, phonetic transcription encoding, and georeferencing of linguistic points. The first results highlight the potential of DigitALI for socio-historical research, enabling large-scale analyses of dialectal variation.